PROBLEMATIKA STREET PHOTOGRAPHY DALAM PERSPEKTIF ESTETIKA SENI DAN HUKUM HAK KEKAYAAN INTELEKTUAL - Desy Sugianti; Miftah Ulumudin Tsani; Dedi Sugiyanto (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This study examines street photography in Indonesia as a visual art practice that engages freedom of expression, ethical considerations, and Intellectual Property Rights (IPR). Street photography functions not only as documentation of everyday life in public spaces but also as a medium for expressing social conditions, cultural dynamics, and urban life. Advances in digital technology and social media have facilitated the processes of image capture and dissemination, thereby increasing public access to street photography works. However, these developments have also generated legal and ethical issues. From a legal perspective, photographers hold copyright over photographic works as original creations, including both moral rights and economic rights. Nevertheless, street photography practices frequently involve photographing individuals without prior consent, which may give rise to issues concerning the right to privacy and the right to one’s image. These issues become more pronounced when photographs are used for commercial purposes or widely disseminated through digital media. This study employs a qualitative method with a normative–interpretative legal approach through the analysis of copyright regulations, legal concepts of privacy, and relevant literature. The findings indicate that the existence of public space does not eliminate the ethical responsibility of photographers. Although copyright resides with the photographer, respect for the rights and dignity of photographic subjects must be upheld. The study concludes that street photography practices in Indonesia require a balance between creative freedom, ethical awareness, and legal understanding in order to develop responsibly and sustainably.